Molecular dynamics simulations of the delta and omicron SARS-CoV-2 spike – ACE2 complexes reveal distinct changes between both variants - Socher, Eileen; Heger, Lukas; Paulsen, Friedrich; Zunke, Friederike; Arnold, Philipp (Computational and Structural Biotechnology Journal, 2022)
SARS-CoV-2, the virus causing the COVID-19 pandemic, changes frequently through the appearance of mutations constantly leading to new variants. However, only few variants evolve as dominating and will be considered as “Variants of Concern” (VOCs) by the world health organization (WHO). At the end of 2020 the alpha (B.1.1.7) variant appeared in the United Kingdom and dominated the pandemic situation until mid of 2021 when it was substituted by the delta variant (B.1.617.2) that first appeared in India as predominant. At the end of 2021, SARS-CoV-2 omicron (B.1.1.529) evolved as the dominating variant. Here, we use in silico modeling and molecular dynamics (MD) simulations of the receptor-binding domain of the viral spike protein and the host cell surface receptor ACE2 to analyze and compare the interaction pattern between the wild type, delta and omicron variants. We identified residue 493 in delta (glutamine) and omicron (arginine) with altered binding properties towards ACE2.<br
Keywords: COVID-19; SARS-CoV-2; B.1.427/B.1.429; B.1.617.2; B.1.617.1; B.1.1.529; Epsilon variant; Delta variant; Kappa variant; Omicron variant; VOC; Spike protein; Receptor-binding domain; ACE2; Receptor interface; Molecular dynamics simulations